Unions and Workers’ Welfare in Chinese Firms - Yao, Yang; Zhong, Ninghua (Journal of Labor Economics, 2013)
Based on a survey of 1, 268 firms in 12 cities, this article empirically studies unions' effects on worker welfare in China. Regressions carried out on a rich set of specifications show that unionization is significantly associated with higher hourly wages and larger pension coverage and weakly associated with lower monthly working hours. Further econometric analysis finds that unions promote individual and collective contracts. The effect of collective contracts vanishes when unions are present, whereas individual contracts have independent and positive effects. In addition, unions have effects on workers' welfare independent of collective and individual contracts.